All roads lead to Rome: Internationalization strategies of Chinese law firms. Issue 2 (29th June 2019) - Li, Jing
Abstract: On the basis of a hand-collected sample of 123 Chinese law firms, this article offers a comprehensive empirical examination into their globalization efforts. It finds that the majority of the firms have endeavoured to expand overseas than not. The most frequently used strategies are international offices and formal cross-border referral networks. While all law firms are enthusiastic to echo and tag along the government-led 'Going Out' initiatives so as to claim legitimacy for their activities, the firms with secondary or lower tier reputation tend to implement it on a more substantive level. Overall, Chinese law firms are still at the initial stage of their internationalization process, and there are considerable discrepancies between actual practices and the formal structures. This is most evident when many of the international offices are in fact associated or merged but subtly marketed as directly invested, thus illustrating that internationalization often carries symbolic value in the eyes of clients. This said, a closer look at the overseas offices with resident lawyers reveals that Chinese law firms are often also calculative entrepreneurs, who know where their competitiveness lies. They purposefully organize their offices to focus on trade route underpinned work, especially the niche market of the outbound Chinese SMEs. As such, pragmatism, entrepreneurship, and state power dynamically interact with each other in shaping the internationalization trajectories of Chinese law firms.